Paraguay : 2022 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2022)
After two consecutive years of GDP decline driven by external shocks, Paraguay's economy rebounded in 2021. In 2019, drought and flooding reduced economic growth to -0.4 percent. In 2020, the impact of the pandemic on the secondary and tertiary sectors was partly compensated by a rebound of agriculture and an extensive emergency package, and GDP fell by only 0.8 percent. Growth rebounded to 4.2 percent in 2021, but heatwaves and a severe drought decelerated the recovery and have limited 2022 growth prospects, though a recovery is projected for 2023 and the medium-term. While the loss of agricultural export revenue is affecting Paraguay's balance of payments in 2022, the external position in 2021 was stronger than the level implied by fundamentals and desirable policies.